ҚАРАҚАЛПАҚСТАН СУЎРЕТЛЕЎ ӨНЕРИ ТИЙКАРЫНДА ТАЛАБАЛАРДЫҢ КӨРКЕМ-ДӨРЕТИЎШИЛИК УҚЫБЫН РАЎАЖЛАНДЫРЫЎ ЖОЛЛАРЫ - Уразимова, Т.В. (SCIENCE and SOCIETY, 2020)
The article is devoted to the modern content and role of the educational process. Today attention increased in modern society to problem of the continous artistic formation. Not the last role is played here by aesthetic education, contributing to enhance the development of philosophy, intellectual and creative potential of the individual. Therefore, the process of education should be based on creating conditions for education of creative personality, ready for a dialogue, collaboration and co-creation in various spheres of life.